Dietary Whey and Casein Differentially Affect Energy Balance, Gut Hormones, Glucose Metabolism, and Taste Preference in Diet-Induced Obese Rats. Issue 10 (26th August 2015) - Pezeshki, Adel; Fahim, Andrew; Chelikani, Prasanth K
Abstract: Background: Dietary whey and casein proteins decrease food intake and body weight and improve glycemic control; however, little is known about the underlying mechanisms. Objective: We determined the effects of dietary whey, casein, and a combination of the 2 on energy balance, hormones, glucose metabolism, and taste preference in rats. Methods: In Expt. 1, Obesity Prone CD (OP-CD) rats were fed a high-fat control diet (33% fat energy) for 8 wk, and then randomly assigned to 4 isocaloric dietary treatments ( n = 12/group): the control treatment (CO; 14% protein energy from egg white), the whey treatment (WH; 26% whey + 14% egg white), the casein treatment (CA; 26% casein + 14% egg white), or the whey plus casein treatment (WHCA; 13% whey + 13% casein + 14% egg white) for 28 d. Measurements included food intake, energy expenditure, body composition, metabolic hormones, glucose tolerance and key tissue markers of glucose and energy metabolism. In Expt. 2, naïve OP-CD rats were randomly assigned to 3 groups ( n = 8/group). During an 8 d conditioning period, each group received on alternate days either the CO or WH, CO or CA, or CO or WHCA. Subsequently, preferences for the test diets were assessed on 2 consecutive days with food intake measurements at regular intervals. Results: In Expt. 1, food intake was decreased by 17–37% for the first 14 d in the WH and CA rats, and by 18–34% only for the first 4 d in the WHCA compared with the CO rats. Fat mass decreased by 21–28% for the WH rats and 17–33% for the CA rats from day 14 onward, but by 30% only on day 28 in WHCA rats, relative to CO rats. Thus, food intake, body weight, and fat mass decreased more rapidly in WH and CA rats than in WHCA rats. Energy expenditure in WH rats decreased for the first 4 d compared with CA and WHCA rats, and for the first 7 d compared with the CO rats. Circulating leptin, glucose-dependent insulinotropic polypeptide, interleukin 6, and glucose concentrations were lower in WH, CA, and WHCA rats than in CO rats. Plasma glucagon-like peptide 1 concentrations were greater in WH than in CA or WHCA rats. The improvements in glucose tolerance were greater in WH than in WHCA rats. The plasma membrane glucose transporter 4 (GLUT4)–to-total GLUT4 ratio in skeletal muscle was greater in CA and WHCA rats than in CO rats; other markers of glucose and energy metabolism in the adipose and cardiac tissues did not differ. In Expt. 2, during 4 conditioning trials, daily food intake was decreased in WH, CA, and WHCA rats by 26–37%, 30–43%, and 23–33%, respectively, compared with CO rats. Preferences for WH and CA rats were 45% and 31% lower, respectively, than those for CO rats, but that for WHCA rats did not differ. Conclusion: Together, these data demonstrate that in obese rats, whey, casein, and their combination improve energy balance through differential effects on food intake, taste preference, energy expenditure, glucose tolerance, and gut hormone secretion.